The influence of the microfibril angle on wood stiffness: a continuum micromechanics approach - Hofstetter, Karin; Hellmich, Christian; Eberhardsteiner, Josef (Computer Assisted Methods in Engineering and Science, 2022)
Wood exhibits an intrinsic structural hierarchy. It is composed of wood cells, which are hollow tubes oriented in the stem direction. The cell wall is built up by stiff cellulose fibrils which are embedded in a soft polymer matrix. This structural hierarchy is considered in a four-step homogenization scheme, predicting the macroscopic elastic behavior of different wood species from tissue-specific chemical composition and microporosity, based on the elastic properties of nanoscaled universal building blocks. Special attention is paid to the fact that the fibrils are helically wound in the cell wall, at an angle of 00 - 300, generally denoted as microfibril angle. Consideration of this microfibril angle in the continuum micromechanics model for wood is mandatory for appropriate prediction of macroscopic stiffness properties, in particular of the longitudinal elastic modulus and the longitudinal shear modulus. The presented developments can be readily extended to the prediction of poroelastic properties, such as Biot and Skempton coefficients.